Answer: 214.28
Step-by-step explanation:
Answer:
B. ![f\left(x\right)=\frac{x}{\left(x+4\right)\left(x-1\right)}](https://tex.z-dn.net/?f=f%5Cleft%28x%5Cright%29%3D%5Cfrac%7Bx%7D%7B%5Cleft%28x%2B4%5Cright%29%5Cleft%28x-1%5Cright%29%7D)
Step-by-step explanation:
I graphed this function on the graph below and it matched the graph you have.
Answer:
-7
Step-by-step explanation:
Answer:
![h(x) = \frac{1}{2} x+ 5](https://tex.z-dn.net/?f=h%28x%29%20%3D%20%5Cfrac%7B1%7D%7B2%7D%20x%2B%205)
Step-by-step explanation:
To find the inverse of a function, simply switch the 'x' and 'y' variables. Substitute in 'y' in the place of f(x) for this purpose:
y = 2x - 10
Switch positions:
x = 2y - 10
Add '10' to both sides to begin simplifying:
x + 10 = 2y
Divide both sides by 2:
![y= \frac{x+10}{2}](https://tex.z-dn.net/?f=y%3D%20%5Cfrac%7Bx%2B10%7D%7B2%7D)
This can be rewritten as:
![y = \frac{1}{2} x+ 5](https://tex.z-dn.net/?f=y%20%3D%20%5Cfrac%7B1%7D%7B2%7D%20x%2B%205)
Therefore, the inverse of the function is:
![h(x) = \frac{1}{2} x+ 5](https://tex.z-dn.net/?f=h%28x%29%20%3D%20%5Cfrac%7B1%7D%7B2%7D%20x%2B%205)